2013
DOI: 10.1093/cid/cit004
|View full text |Cite
|
Sign up to set email alerts
|

Is Frequent CD4+T-Lymphocyte Count Monitoring Necessary for Persons With Counts ≥300 Cells/µL and HIV-1 Suppression?: Figure 1.

Abstract: Among patients infected with human immunodeficiency virus (HIV), those with HIV-1 RNA <200 copies/mL and CD4 counts ≥300 cells/µL had a 97.1% probability of maintaining durable CD4 ≥200 cells/µL for 4 years. When non-HIV causes of CD4 lymphopenia were excluded, the probability rose to 99.2%. Our data support less frequent CD4 monitoring during viral suppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 8 publications
1
68
0
2
Order By: Relevance
“…[10] Similar studies among adults in Uganda [11] and children in SA [12] have confirmed that the CD4 + cell count does not decline significantly in the vast majority of patients who respond to treatment and are virologically suppressed. Reflecting this growing evidence base, the WHO released a technical document in March 2014 summarising the considerations in support of a move towards stopping routine CD4 + monitoring where VL monitoring is available.…”
Section: Time To Reduce Cd4 + Monitoring For the Management Of Antirementioning
confidence: 64%
“…[10] Similar studies among adults in Uganda [11] and children in SA [12] have confirmed that the CD4 + cell count does not decline significantly in the vast majority of patients who respond to treatment and are virologically suppressed. Reflecting this growing evidence base, the WHO released a technical document in March 2014 summarising the considerations in support of a move towards stopping routine CD4 + monitoring where VL monitoring is available.…”
Section: Time To Reduce Cd4 + Monitoring For the Management Of Antirementioning
confidence: 64%
“…17 A cohort study from the USA noted that of 832 patients followed for a median of 7·7 years, patients with an initial CD4 count of 300 cells per μL or more who were virologically suppressed (<200 copies/mL) had a probability of a durable CD4 count of 200 cells per μL or more at year 5 of 99·2% (95% CI 97·4-99·7), after exclusion of non-HIV causes of lymphopenia. 16 Two studies from the UK support these fi ndings. In the fi rst study, 166 patients who were stable (CD4 >500 cells per μL and virologically suppressed [<50 copies/mL]) were followed for a median of 47 weeks; only fi ve (3%) patients had a reduction in CD4 count less than 350 cells per μL and these reductions were again transient, with all CD4 measures greater than 350 cells per μL at subsequent visit.…”
Section: Art Monitoringmentioning
confidence: 94%
“…Several studies have recently suggested that CD4 cell count monitoring has little added value in situations where viral load is available and patients are virologically suppressed. [16][17][18] In September, 2013, WHO held an expert consultation on the future role of CD4 testing for ART monitoring. We summarise the evidence and experience shared and the conclusions reached at this consultation.…”
Section: -10mentioning
confidence: 99%
“…4 Additionally, a retrospective cohort study involving 1820 patients with 25 463 paired viral load-CD4 measurements showed that patients who maintained virologic suppression (< 200 copies/ mL) had a 97.1% probability of maintaining a CD4 count of 200 cells/µL or greater for four years. 5 When non-HIV-related causes of decline in CD4 count were excluded, this probability increased to 99.2%. 5 Therefore, the decline in this patient's CD4 count is likely of no immediate or long-term clinical importance.…”
Section: Is the Decline In This Patient's Cd4 Count Clinically Importmentioning
confidence: 99%
“…5 When non-HIV-related causes of decline in CD4 count were excluded, this probability increased to 99.2%. 5 Therefore, the decline in this patient's CD4 count is likely of no immediate or long-term clinical importance.…”
Section: Is the Decline In This Patient's Cd4 Count Clinically Importmentioning
confidence: 99%